Comparative Evaluation of the Efficacy of Human Periostin and Enamel Matrix Derivative (Emdogain®) on Proliferation and Migration of Periodontal Ligament Fibroblasts - Swastik Mishra; Jothi M. Varghese; Shama Prasada Kabekkodu (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To explore the proliferative and wound-healing potential of Periostin and Emdogain® on periodontal fibroblasts. Material and Methods: Human PDL (hPDL) fibroblasts were cultured and treated with two biological agents, Emdogain® and Periostin. The Dulbecco's Modified Eagle Medium (DMEM) served as the control. The cytotoxic effects of Emdogain® and Periostin were analyzed using the Clonogenic assay. Cell viability was estimated using the CCK-8 assay. Further, the migratory potential of the hPDL fibroblasts was assessed using the scratch migration assay. Results: The results showed that 1/1000 dilution of Emdogain® and 1/10 dilution of Periostin had the highest cell survival fraction (p<0.05). In the CCK-8 assay, Emdogain® displayed maximum cell viability compared to Periostin (p=0.000) and control (p=0.006). The PDL fibroblasts' migratory rate corresponded to the experimental agents' wound-healing potential. Emdogain® presented with earlier wound closure compared to Periostin (p=0.002) and control (p=0.000). Conclusion: Thus, based on the results of this study, Periostin may be a viable biologic agent for promoting periodontal regeneration.